Becoming Communist: Ideals, Dreams, and Nightmares. Issue 1 (1st March 2019) - Ruthchild, Rochelle Goldberg
Abstract : Kelly Hignett, Melanie Ilic, Dalia Leinarte, and Corina Snitar, Women's Experiences of Repression in the Soviet Union and Eastern Europe, London: Routledge, 2018, xiii, 196 pp., 123.09 (hardback), ISBN 978-1-138-04692-4. Lisa Kirschenbaum, International Communism and the Spanish Civil War: Solidarity and Suspicion, Cambridge: Cambridge University Press, 2015, xiii, 278 pp., 29.99 (paperback), ISBN: 978-1-131-622690-2.